The ClpXP Protease Is Responsible for the Degradation of the Epsilon Antidote to the Zeta Toxin of the Streptococcal pSM19035 Plasmid - Brzozowska, Iwona (American Society for Biochemistry and Molecular Biology, 2014)
Most bacterial genomes contain different types of toxin-antitoxin (TA) systems. The ω-ϵ-ζ proteinaceous type II TA cassette from the streptococcal pSM19035 plasmid is a member of the ϵ/ζ family, which is commonly found in multiresistance plasmids and chromosomes of various human pathogens. Regulation of type II TA systems relies on the proteolysis of antitoxin proteins. Under normal conditions, the Epsilon antidote neutralizes the Zeta toxin through the formation of a tight complex. In this study, we show, using both in vivo and in vitro analyses, that the ClpXP protease is responsible for Epsilon antitoxin degradation. Using in vivo studies, we examined the stability of the plasmids with active or inactive ω-ϵ-ζ TA cassettes in B. subtilis mutants that were defective for different proteases. Using in vitro assays, the degradation of purified His(6)-Epsilon by the His(6)-Lon(Bs), ClpP(Bs), and ClpX(Bs) proteases from B. subtilis was analyzed. Additionally, we showed that purified Zeta toxin protects the Epsilon protein from rapid ClpXP-catalyzed degradation.